ANALISIS STRATEGI PENGEMBANGAN USAHA JASA TRANSPORTASI ONLINE (STUDI PADA USTREET LAMPUNG) - Afifi, Haris Abi; Aprilani, Deddy; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine alternative business development strategies in online transportation services UStreet Lampung by analyzing the internal and external environment. In this study using a qualitative approach with data collection through observation, documentation and in-depth interviews. Data was taken by using a snowball sampling technique. Then the data obtained is processed and analyzed with the help of the internal factor evaluation matrix (IFE), the external factor evaluation (EFE), and the SWOT matrix. The results in this study are that UStreet Lampung online transportation services are in quadrant I, namely the SO strategy or aggressive growth strategy. In this position, it means that the company is in a very profitable position where the company has internal strength to take advantage of and seize opportunities as much as possible.